Tích hợp khuôn mẫu công nghệ - tổ chức - môi trường và quan điểm nguồn lực trong nghiên cứu về sự chấp nhận sử dụng phần mềm kế toán và hệ thống ERP - Dau Thi Kim , Thoa; Pham Tra , Lam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
Application software in accounting information systems is increasingly being implemented for providing information and enhancing competitiveness. The enterprises demand knowledge to evaluate factors affecting the adoption of accounting software and ERP systems, and their impact on business performance. This study integrated the Technology – Organization – Environment framework and the Resource-based view to develop a path model for the adoption of accounting software and ERP systems. Through PLS analysis from the survey results of 203 enterprises, the authors confirm that the adoption of accounting software and ERP system has a significant influence on the performance of enterprises. Four factors including attitude towards use, observability, organizational culture, and ICT infrastructures explain 51.7 percent variation of behavioral intention use accounting software/ERP systems. These findings have provided implications that guide accounting information systems scholars and practitioners to improve the adoption of accounting software/ERP systems and therefore, enhance their impact on firm performance.